Reasons, reflection, and repugnance - McConnell, D (Oxford Scholarship Online, 2016)
In the debate about the pros and cons of human enhancement, proponents of enhancement (so-called ‘liberals’) often accuse their opponents (so-called ‘conservatives’) of substituting emotion for reason. In this they are relying on an age-old dichotomy between reason and emotion that has a long popular and philosophical history. Plato’s picture of reason as the charioteer controlling the turbulent horses of the passions has had a significant influence (though its popular version ignores Plato’s reservations.) Cognitive psychologists and neuroscientists have recently joined the fray and sought to examine the role of reason on the one hand and emotion on the other in moral outlooks and decisions. This chapter examines the contrast between reason and emotion and, while noting many ambiguities in both concepts, will argue that much of the separation of reason and emotion that underpins the debate is misguided.